Strategi Peningkatan Kualitas SDM sebagai Pasukan Pemelihara Perdamaian di Pusat Misi Pemeliharaan Perdamaian TNI (PMPP TNI) - Hengki Handoyo (Publikasi Indonesia, 2026)
The aim of this research is to determine strategies for improving the quality of human resources as peacekeepers at the TNI Peacekeeping Mission Center (PMPP TNI). This research uses qualitative methods to explore strategies for enhancing the quality of human resources serving as peacekeepers at the TNI Peacekeeping Mission Center. Through in-depth analysis of relevant texts and contexts, this research reveals the importance of fostering quality leadership and planned human resource development in the context of global peace missions. The research findings highlight the complexity of the challenges faced in implementing this strategy, including the necessity of international collaboration in knowledge and technology exchange. The implications of these findings indicate the need for a holistic and targeted approach to achieve the goal of enhancing the quality of human resources in peacekeeping training. Additionally, it underscores the importance of recognizing that peacekeeping training technology necessitates cross-border collaboration to attain optimal peacekeeping training independence. This research provides valuable insights for policymakers and practitioners in formulating strategies to improve the quality of human resources as part of endeavors to uphold world peace.